Investigating Students’ Perception on Online Learning: A Comparative Study of Gender-Based EFL Learning During Covid-19 Pandemic - Ibrahim Ibrahim; Muhaiminah Akib; Eva Fadilah Lebeharia; Firman Saleh (Universitas Muhammadiyah Sorong, 2021)
This study aimed to to find out students' perceptions of online learning based on gender and level of education. This research was conducted at Universitas Muhammadiyah Sorong. This study used qualitative research method and used descriptive qualitative as the design. Participants in this study were 22 students. The instrument used were questionnaire and interview. The data analysis technique used in this study was descriptive statistics and used a five-point Likert scale for the questionnaire. Also, the data that had been collected will be calculated by using Simple Tabulation. Result showed that both male and female have a positive tendency towards implementing online learning in terms of teaching materials and the students’ interaction. The result showed that both male and female junior high school students have a positive tendency towards implementing online learning in terms of the dimensions of English teaching materials. From the dimensions of the learning environment and student interaction, male students' perceptions tend to be more positive than female students. Based on the result it can be concluded that students have positive perception on online learning.